Penggunaan Metode AHP dalam Menentukan Cryptocurrency untuk Investasi - Farrell Ivander Daviano Siwy; Malvin Setiadi Dharmawan; Hendra Mayatopani (Jurnal Teknologi Informasi dan Multimedia, 2023)
The use of digital currency or cryptocurrencies has been common since 2018. However, its use as an investment instrument is different from the conventional currency recognized by the state, this is because a cryptocurrency appeared by a number of organizations/companies and its value does not depend on the economic condition of a country, but on the status of a company/issuer of a digital currency. Difficulty predicting liability and growth creates computational needs to determine which digital currencies are suitable for investment, so in this study, 11 digital currencies are used to try out. Experiment with AHP calculations to get the best digital currency to use as an investment tool. This calculation translates into IOT Coin against other famous digital currencies, such as Bitcoin or Ethereum.